Superresolution light microscopy shows nanostructure of carbon ion radiation-induced DNA double-strand break repair foci - Lopez Perez, Ramon; Best, Gerrit; Nicolay, Nils; Roßberger, Sabrina; Weber, Klaus-Josef; Cremer, Christoph; Huber, Peter E. (The FASEB journal, 2016)
Carbon ion radiation is a promising new form of radiotherapy for cancer, but the central question about the biologic effects of charged particle radiation is yet incompletely understood. Key to this question is the understanding of the interaction of ions with DNA in the cell’s nucleus. Induction and repair of DNA lesions including double-strand breaks (DSBs) are decisive for the cell. Several DSB repair markers have been used to investigate these processes microscopically, but the limited resolution of conventional microscopy is insufficient to provide structural insights. We have applied superresolution microscopy to overcome these limitations and analyze the fine structure of DSB repair foci. We found that the conventionally detected foci of the widely used DSB marker γH2AX (Ø 700-1000 nm) were composed of elongated subfoci with a size of ∼100 nm consisting of even smaller subfocus elements (Ø 40-60 nm). The structural organization of the subfoci suggests that they could represent the local chromatin structure of elementary DSB repair units at the DSB damage sites. Subfocus clusters may indicate induction of densely spaced DSBs, which are thought to be associated with the high biologic effectiveness of carbon ions. Superresolution microscopy might emerge as a powerful tool to improve our knowledge of interactions of ionizing radiation with cells.—Lopez Perez, R., Best, G., Nicolay, N. H., Greubel, C., Rossberger, S., Reindl, J., Dollinger, G., Weber, K.-J., Cremer, C., Huber, P. E. Superresolution light microscopy shows nanostructure of carbon ion radiation-induced DNA double-strand break repair foci.
Gesehen am 20.11.2018